PENERAPAN MODEL KOOPERATIF BERPIKIR, BERPASANGAN DAN BERBAGI (KOPI PAGI) DALAM MENINGKATKAN KETERAMPILAN BERBICARA DAN HASIL BELAJAR MUATAN IPA SISWA KELAS IV SEKOLAH DASAR - Esti Untari; Sukamti; Lilik Bintartik; Sri Estu Winahyu, Sigit Wibowo, Riski Solehariyah, Zulfa Aji Mukti (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article examines the effect of the KOPI PAGI model on fourth-grade students’ speaking skills and learning outcomes at SDN Bendogerit 1 Blitar. The research design used a quasi-experimental research design with a non-equivalent control group design. The research was conducted in two classes, class 4A as the control class and class 4B as the experimental class. The average score of students’ learning outcomes in the control class using the conventional learning model was 57.78 increased to 65.3. Whilst the students’ learning outcomes in the experimental class by applying the KOPI PAGI learning model increased from 60.2 to 80.8. The average score result of students' speaking skills in the control class was 46.41 increased to 65.37. Meanwhile, the average score results of students' speaking skills in the experimental class were 57.44 that increased to 74.6. After testing the N-Gain score, the results showed that the average score in the control class was 21.69% as classified as ineffective. Whilst the average score in the experimental class was 58.12% as classified as quite effective. It is concluded that the KOPI PAGI model could improve students' learning outcomes and speaking skills. In addition, the KOPI PAGI model was more effectively applied to changes in energy and alternative resources learning material for the fourth-grade students of SDN Bendogerit 1 Blitar.